PERBANDINGAN MOTIVASI BELAJAR MAHASISWA S1 KEPERAWATAN ANTARA PEMBELAJARAN DARING DENGAN TATAP MUKA - Henny Syapitri; Adventy Riang Bevy Gulo; Normi Parida Sipayung (Jurnal Online Keperawatan Indonesia, 2021)
The Covid-19 pandemic has made many parties seek to participate in overcoming the spread of both the government and all levels of society. One of the efforts made is by issuing an online learning policy to prevent the spread of Covid-19 through the Minister of Education and Culture Circular No. 36962/MPK.A/HK/2020. This condition requires lecturers to carry out the process online. All literature indicates that not all students will be successful in online learning, this is due to differences in learning environment factors and student characteristics. One of the successes in learning is related to the motivation of students. The purpose of this study is to determine the difference between student learning motivation and online and face-to-face learning. The research method is quantitative with a comparative research type with a population of 216 people. The sampling technique is stratified random sampling technique with a total sample of 140 people. Chi-Square statistical test. The results show that there is a comparison of student learning motivation between online and face-to-face learning, the p value = 0.008 < 0.05. Based on the results of the research and discussion, it can be concluded that there is a comparison of the learning motivation of undergraduate nursing students between online and face-to-face learning at Sari Mutiara University Indonesia.